Modelling Dynamic Volatility Spillovers from the U.S. to the BRIC Countries’ Stock Markets During the Subprime Crisis - Singh, Amanjot; Kaur, Parneet (Indian Journal of Finance, 2015)
The term ’BRIC’ is a collection of Brazil, Russia, India, and China: the most promising emerging markets. The global investors at the time of making investments and building portfolios across different countries should consider the interlinkages that exist between the countries or the assets concerned. The interlinkages make the stock markets in different countries to co-move in the short as well as the long run, thereby leading to spillover of the returns and volatility. The present study attempted to model the dynamic volatility spillover from the U.S. market to the BRIC (Brazil, Russia, India, and China) countries’ stock markets during the subprime crisis by employing the ARMA E-GARCH (1,1) model. The results from the E-GARCH (1,1) model supported the spillover of the U.S. volatility to the Brazilian market only. The study revealed that the volatility in the U.S. market did not have a direct impact on the Russian, Indian, and Chinese stock markets.